Comment on "Global pattern of nest predation is disrupted by climate change in shorebirds" - Bulla, Martin; Reneerkens, Jeroen; Weiser, Emily L; Sokolov, Aleksandr; Taylor, Audrey R; Sittler, Benoît; McCaffery, Brian J; Ruthrauff, Dan R; Catlin, Daniel H; Payer, David C; Ward, David H; Solovyeva, Diana V; et al. (Science (New York, N.Y.), 2019)
Kubelka et al (Reports, 9 November 2018, p. 680) claim that climate change has disrupted patterns of nest predation in shorebirds. They report that predation rates have increased since the 1950s, especially in the Arctic. We describe methodological problems with their analyses and argue that there is no solid statistical support for their claims.
Keywords: Arktida; Animals; Arctic Regions; hnízdění; predátorské chování; zvířata; Climate Change; Nesting Behavior; Predatory Behavior; klimatické změny